The influence of asset specificity on farmers’ willingness to participate in fallow from the perspective of farmer differentiation - Zhang, Siyang; Xie, Xianxiong; Luo, Yu; Liu, Xiaoqi; Zhao, Minjuan (Frontiers in Environmental Science, 2023)
Fallow is an important institutional guarantee for green agricultural development and an important measure to promote rural revitalization. Asset specificity is a crucial factor that affects farmers’ willingness to participate in fallow. In order to improve farmers’ willingness of to fallow and promote the long-term promotion of fallow system, based on the perspective of farmer differentiation, a total of 1240 micro survey data in four cities of Gansu province was used to quantify the asset specificity by the entropy method. A multivariate ordered Logit model and a double-hurdle model were established to explore the effects of asset specificity on the willingness of farmers with different degrees of differentiation. The results show that: (1) There are differences in fallow willingness among different types of farmers. The fallow willingness of non-farmers and II part-time farmers is generally stronger than that of pure farmers and I part-time farmers. (2) Geographical location specificity has a significant negative impact on the fallow willingness of the four types of non-fallow farmers, and has significant negative impacts on the subsequent fallow willingness and fallow degree of the four types of fallow farmers. (3) Physical asset specificity has a significant negative effect on the fallow willingness of pure farmers, I part-time and II part-time farmers among non-fallow farmers, but has little effect on the subsequent fallow willingness of fallow farmers. (4) Human capital specificity has a significant negative impact on the fallow willingness of the four types of non-fallow farmers, and has a significant negative impact on the subsequent fallow willingness and fallow degree of the four types of fallow farmers.